Nutritional Status of Children in Three Pre-elementary Schools in Medan, North Sumatera Abstract - Abdul Gani; Erliana Malik Miraza; Iskandar Z. Lubis; Endang D. Hamid; Sjarjikat Tarigan (Indonesian Pediatric Society, 1992)
Anthropometric measurements have been taken on 162 children of Methodist, Dharma Wanita USU and Aisyiah pre-elementary schools in Medan to assess their nutritional status. This study was done cross sectionally from january to February 1990. The nutritional status of those children were then compared among those schools with the assumption that father's income and educational level of mothers were different. By the parameters of W!A, HI A. q.nd WIH it showed that the nutritional status of children in the pre-elementary schools were generally quite good. Using parameters W/A and W/H there was a significant difference between the children in Methodist and in Aisyiah (p <0.001). University graduated mothers could be found in Dharma Wan ita USU, whereas in Methodist and Aisyiah pre-elementary schools the mothers were mostly secondary high school graduates. Father's income above Rp. 150.000,- could be found in Methodist pre-elementary school subsequently followed by Dharma Wanita USU pre-elementary schools, whereas in A isyiah pre-elementary school the father's income was mostly between Rp. 100.000,and Rp. 149.999,-. By using the Water/ow classification we found 9.88% children with acute Protein Calorie Malnutrition, whereas chronic Protein Calorie Malnutrition only 2.46%. The nutritional status of children in the three pre-elementary schools could be concluded as good.